IMMUNOLOGICAL CHARACTERISTICS OF PSORIASIS (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article provides a comprehensive analysis of the immunopathogenesis, epidemiology, etiologic factors, and clinical manifestations of psoriasis. The central role of the IL-23/IL-17 axis and the interaction between keratinocytes and Th17 cells are substantiated. Diagnostic approaches, including the application of PASI, BSA, and DLQI indices, are highlighted. The systemic nature of psoriasis, its association with comorbid conditions, and the efficacy of biologic therapy are discussed based on scientific literature, emphasizing the importance of individualized treatment strategies. The results underscore the significance of early diagnosis and monitoring in disease management and provide a basis for developing preventive measures.
Keywords: Psoriasis, immunology, IL-17, IL-23, Th17 cells, pathogenesis, keratinocytes, biologic therapy.